Новi нанокомпозити полiмер–окис свинцю для застосування в радiацiйному захисту - Hashim, A.; Hadi, A. (Publishing house "Academperiodika", 2018)
Polymer nanocomposites have been used in many applications such as a fabrication of protective enclosures for humans and devices at nuclear power plants and hospitals. The aim of this paper is the preparation of novel polymer nanocomposites with high linear attenuation coefficients for nuclear radiation shielding. We have produced the nanocomposites of polyvinyl alcohol, polyacrylic acid, and lead oxide nanoparticles with various concentrations of components and have studied their optical properties. As the concentration of PbO2 nanoparticles increases, the absorbance of a polymer blend and the optical constants increase, whereas energy band gap decreases. The tests of the nanocomposite for the gamma radiation shielding showed that it has high attenuation coefficients for gamma radiation.